Identifying metadata elements in computer forensics in Malaysia/ Alwi Mohd Yunus, Nor Sakila Asnawi and Irwan Kamaruddin Abdul Kadir - Mohd Yunus, Alwi; Asnawi, Nor Sakila; Abdul Kadir, Irwan Kamaruddin (Faculty of Information Management, 2021)
Computer forensics is a scientific investigation and analysis technique toward crimes in computing environment. Different set of skills and methods are needed in conducting computer forensics investigation process. Metadata is one of the requirements in computer forensics investigation. This study attempts to gain greater understanding on the use of metadata elements in computer forensics investigation especially in Malaysia. Metadata elements are required to extract information from the evidence without delaying any important information. Therefore, to give impact on the acceptance of electronic evidence in the court of law. Through qualitative method, face-to-face interview was conducted with two agencies responsible in computer forensics investigation namely, the CyberSecurity Malaysia and the Royal Police Malaysia (RPM). An analysis was done manually after the interviews were conducted. Based on the interviews and analysis, the study found that both agencies agreed on the importance of the right metadata elements needed in computer forensics investigation. This paper is written to give overall view of the study.